Performance-based evaluation : tools and techniques to measure the impact of training - Hale, Judith A. (San Francisco : Jossey-Bass, 2002)
The book contains a wealth of information including suggestions on how to measure both hard and soft skills; guidance on measuring required and mandated programmes; ideas for measuring elective training and employee relations programmes; procedures for comparing different delivery systems; information on how to sample people and documents and tips for both collecting data and information on analyzing data using descriptive and inferential statistics.
CD-ROM instructions on p. 289.
Includes bibliographical references and index.
rpm 10/06/15
Loans
5 1/2 in. CD-Rom included., Microsoft Windows 95 or later; Macintosh with 68020 or higher processor.
Keywords: Employees -- Training of -- Evaluation